2015
DOI: 10.1039/c4sm02564d
|View full text |Cite
|
Sign up to set email alerts
|

Multi stimuli-responsive hydrogel microfibers containing magnetite nanoparticles prepared using microcapillary devices

Abstract: Extensive research efforts have been devoted to the development of hydrogel microfibers for tissue engineering, because the vascular structure is related to the transport of nutrients and oxygen as well as the control of metabolic and mechanical functions in the human body. Even though stimuli-responsive properties would enhance the potential applicability of hydrogel microfibers for artificial tissue architectures, previous studies of their fabrication have not considered changes in the microfibers in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 38 publications
1
61
0
Order By: Relevance
“…MNP-containing copolymer and PNIPAm beads were found to show characteristic temperature-dependent volume phase transitions. In accordance with the previous study, [ 24,29 ] PNIPAm/ MNP beads exhibited a volume phase transition near 32 °C. As expected, p(NIPAm-co -VP)/MNP showed a higher LCST than PNIPAm/MNP due to the incorporation of hydrophilic VP into the PNIPAm backbone, and the temperature range for rapid volume decrease shifted to higher temperatures with increasing VP composition of the hydrogel ( Figure S1, Supporting Information).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…MNP-containing copolymer and PNIPAm beads were found to show characteristic temperature-dependent volume phase transitions. In accordance with the previous study, [ 24,29 ] PNIPAm/ MNP beads exhibited a volume phase transition near 32 °C. As expected, p(NIPAm-co -VP)/MNP showed a higher LCST than PNIPAm/MNP due to the incorporation of hydrophilic VP into the PNIPAm backbone, and the temperature range for rapid volume decrease shifted to higher temperatures with increasing VP composition of the hydrogel ( Figure S1, Supporting Information).…”
Section: Resultssupporting
confidence: 91%
“…[23][24][25]29 ] To demonstrate this point, selected p(NIPAm-co -VP)/MNP beads were irradiated with visible light of 47.5 mW cm −2 for 2 min. We found that only the beads in the irradiated area contracted, while the diameter change in nonirradiated areas was negligible (Figure 4 c,d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After modified with XYZ‐directions, composite hydrogel fibers could be obtained in purpose . In addition, the microfluidic strategy can be used to produce fibers with diverse morphologies and multiple components, such as hollow, thermosensitive, or magneto‐sensitive fibers, by the delicate design of microfluidic structures …”
Section: Shaping Nanocomposite Hydrogelsmentioning
confidence: 99%